Non-communicable disease syndemics: poverty, depression, and diabetes among low-income populations - Mendenhall, Emily; Kohrt, Brandon A; Norris, Shane A; Ndetei, David; Prabhakaran, Dorairaj (The Lancet (British edition), 2017)
The co-occurrence of health burdens in transitioning populations, particularly in specific socioeconomic and cultural contexts, calls for conceptual frameworks to improve understanding of risk factors, so as to better design and implement prevention and intervention programmes to address comorbidities. The concept of a syndemic, developed by medical anthropologists, provides such a framework for preventing and treating comorbidities. The term syndemic refers to synergistic health problems that affect the health of a population within the context of persistent social and economic inequalities. Until now, syndemic theory has been applied to comorbid health problems in poor immigrant communities in high-income countries with limited translation, and in low-income or middle-income countries. In this Series paper, we examine the application of syndemic theory to comorbidities and multimorbidities in low-income and middle-income countries. We employ diabetes as an exemplar and discuss its comorbidity with HIV in Kenya, tuberculosis in India, and depression in South Africa. Using a model of syndemics that addresses transactional pathophysiology, socioeconomic conditions, health system structures, and cultural context, we illustrate the different syndemics across these countries and the potential benefit of syndemic care to patients. We conclude with recommendations for research and systems of care to address syndemics in low-income and middle-income country settings.